Management of Meloidogyne incognita on okra by chemical seed dressing and seed soaking - and B.N. SHUKLA, INDIRA VADHERA, S.P. TIWARI (Indian Phytopathology, 2002)
A trial on seed dressing if okra was carried out in a field naturally infested with M. incognita, in Jabalpur, Madhya Pradesh, India. Seed dressing with carbosulfan, benfuracarb (as Oncol) and triazophos reduced the gall index and increased the yield of okra. Maximum yield was obtained with carbosulfan at 3%. Seed soaking in carbosulfan, triazophos, monocrotophos and zolone [phosalone] reduced the number of galls and egg-masses. Carbosulfan also reduced the invasion of larvae.